La Franquicia como opción de desarrollo para las Empresas en el Perú. - Cortez Salazar, Gardenia Gretell (2019)
Are Franchises a development option for the companies in Peru? Business format franchising is a contract that is established by a legal person who grants to another for a given use of a set of economics instruments (use trade name, trademark, know how, experience, signs and badges, delivery time assets and liabilities), which will enable him to exploit the benefits of a system that already has a cattle market, respecting the conditions of the franchisor and all for an established remuneration. Business contract franchising is a specific and uniform type of commercial activity with significant economic impact around the world. However, compared to its scale in the USA, Australia, EU, Brazil, franchising is not realizing its full potential in Peru. It is disproportionate development in Peru because franchising is not promoting trade among Peruvian entrepreneurs as much as it could and should do. In Peru, the franchise has not reached a high degree of development by various factors. Firstly, the resistance from Peruvian investors who prefers to invest in more "traditional" forms of business and where sharing commitments and mutual obligations, as given in the franchise agreement represents a "risky" chance of success. Also, the Peruvian idiosyncrasy tells us that the Peruvian prefer to bet on a foreign business idea to another Peruvian business idea. One reason is that the franchise system is not promoted enough for the growth of national franchises increase. Secondly, the lack of proper information, the lack of ad hoc legislation and the unwillingness by the state in promoting new forms of investment, have deprived franchise development in accordance with the times. Add to this the fact that our country emerges to a free market economy until the beginning of this decade, mainly due to its statist past and the lack of confidence offered to foreign investors combines. Today, that situation has changed and we have an economy that remains one of the highest growth rates in Latin America, which makes us an attractive place for new businesses and thus potentiate our future. The small domestic production of finished products, the lack of scientific production, the few production of business forms, for the same reason that Peru is developing country makes Peruvians do not rely heavily on a franchise business format created by a Peruvian . The misconception that all foreign products are better should be change due promoting the franchise and make known that the format of business transferred correctly and respecting all the rules becomes a development option that can be created by Peruvian for Peruvian, and for the world. It is proposed that the franchise properly analyzed, promoted and applied becomes a development option for the companies in our country. Also, the following factors should be considered are the consumption characteristics contribute to business expansion, the experience and business predisposition influences the potential of the franchise system, Specific legislation would determine legal certainty in the franchise agreements. The Macroeconomic environment contributes to boost the entrepreneurial development.